Efeito do tratamento térmico e do ácido salicílico na atividade de polifenoloxidase, peroxidase e fenilalanina amônia-liase, nas características físico-químicas e na incidência de patógenos em morangos durante o armazenamento - Coltro, Sidiane (2012)
The strawberry is a fruit that is highly perishable and are very susceptible to physical damage and fungal attack. The use of fungicides has been the primary method for reducing post-harvest diseases. Accordingly, alternative methods free of chemicals must be used in post-harvest to maintain the quality and prolong the life reduce the incidence of fungi. Therefore, this study aimed to evaluate the effect of heat treatment and post-harvest salicylic acid in the response of strawberry-related activities of the enzymes polyphenol oxidase and peroxidase, the contents of total phenols, anthocyanins and ascorbic acid and the incidence of pathogens during storage of fruits. This study was divided into two experiments. In the first experiment, Dover strawberries were treated thermally in an oven at 45°C for 3 hours and stored at 5°C for 1, 7 and 14 days and analyzed. After these periods, the fruit were removed and transferred to the cooling environment at 20°C for 2 days to be analyzed again. We used a completely randomized in factorial scheme (2x6), with 12 treatments and four replicates of 10 berries per tray. In the second experiment, strawberries Dover were heat treated in an oven with forced air at 45°C for 3 hours and after immersed in a solution of salicylic acid 2.0 mM L-1 for 5 minutes; then they were stored under refrigeration (5°C) and after 1,7 and 14 days and transferred to a room at 20°C for 2 days and the be analyzed. The design was completely randomized in factorial scheme (4x3), with 12 treatments and four replications. Were evaluated the activity of polyphenoloxidase, peroxidase, phenylalanine ammonia-lyase, the incidence of fungi, total phenols, anthocyanins, ascorbic acid, pH, titratable acidity, soluble solid and weight loss. It was found that the metabolism postharvest Dover cv. strawberry has been modified by application of heat treatment, because the results showed that the activity of polyphenoloxidase, peroxidase and phenylalanine ammonia-lyase and ascorbic acid, total phenols and anthocyanins, and the incidence of fungi were lower in heat-treated strawberries. The heat treatment resulted in higher acidity, higher soluble solids and lower mass loss. The heat treatment is not provided, according to the incidence of fungi and weight loss, increased shelf life of strawberries, being limited to seven days of storage. However, the addition of salicylic acid to heat treatment was less effective than other treatments for most variables, indicating that it is disadvantageous. However, heat shock alone was more effective in reducing the activity of peroxidase, polyphenoloxidase showed lower activity compared to the control at 7 +2 days and did not differ from other treatments at 14 +2 days, was effective in maintaining high levels phenolic compounds, anthocyanins and ascorbic acid up to 7 +2 days